Chloride transport and induced steel corrosion in recycled aggregate concrete: A review. (3rd May 2021) - Liang, Chaofeng; Cai, Zhedong; Wu, Huixia; Xiao, Jianzhuang; Zhang, Yuming; Ma, Zhiming
Highlights: A systematic review on chloride ingress and steel corrosion in RAC is provided. Revealing the chloride transport mechanism and analysing the influencing factors. Presenting modification methods for decreasing chloride ingress and steel corrosion in RAC. Showing an outlook of further research on chloride ingress in RAC. Abstract: Chloride ingress and resulting steel corrosion are the main reasons leading to durability degradation. A body of literature on chloride transport and steel corrosion in recycled aggregate concrete (RAC) is currently available, but a systematic review has been lacking. This paper presents a critical review of chloride transport in RAC, and the induced steel corrosion behaviour and cracking patterns of reinforced RAC are introduced. Related modification methods are further discussed. The results showed that the incorporated recycled aggregate (RA) increased chloride ingress in RAC, and a time-dependent characteristic was observed for the chloride diffusion coefficient. The lower RA properties led to higher chloride ingress in preparing RAC when RA substitution rates were the same; the induced environmental damage accelerated chloride ingress in RAC. Incorporating RA increased the steel corrosion risk and shortened the initial corrosion time of reinforced RAC, and the cracking pattern of reinforced RAC was different from the cracking pattern of reinforced natural aggregate concrete. Removing and enhancing the adhered old mortar of RA improve the properties of RAC, and various modification methods can be employed to improve the resistance to chloride ingress and steel corrosion in RAC. In particular, a CO2 -curing treatment, which is eco-friendly, is recommended for improving the RA and RAC properties. The study of chloride ingress and steel corrosion in ultra-high performance RAC and 3D-printed RAC should be a focus in further studies.